Penerapan Metode Pembelajaran Fun Learning Untuk Meningkatkan Minat Belajar Peserta Didik - Situlak, Agnes Natalia (Global Journal Teaching Professional, 2023)
This study aims to increase the learning interest of grade 1 students at SDN 1 Rantepao through the application of the Fun Learning method. The type of research used in this study is Classroom Action Research (PTK). PTK is carried out as an effort to overcome problems that arise in the classroom. This research was conducted in 4 (four) stages, namely planning, action implementation, observation, and reflection. The four stages were carried out with the same steps and focused on increasing student interest in learning as the goal of the research conducted. This research was conducted in January 1013 at SDN 1 Rantepao with research subjects in grade 1 students. The research was conducted in 1 (two) cycle and each cycle was conducted three times a meeting. The results showed that there was an increase in student interest in learning in each cycle. This can be seen from the average percentage of student interest in learning in cycle 1 of 54.68% and in cycle 1 has an average percentage of 94.16%, so it can be concluded that the application of the Fun Learning method can increase student interest in learning in class 1 SDN 1 Rantepao.